An Overview of the Development of a Competency Measurement Support Tool - QualPro-CM - Ow, Siew Hock; Hj. Yaacob, Mashkuri (Malaysian Journal of Computer Science, 1998)
Software quality is an important issue in the software development industry. There are three elements that determine the quality of a software system: people, management and technology. Of these three elements, people constitute the most crucial element that determines a successful software outcome. The competency of the people involved in software quality assurance is important. However, there is a lack of appropriate competency measurement models and tools that can be applied for such purpose. This paper highlights the establishment of an indigenous model, the Knowledge, Awareness and Practice (KAP) Model, and the development of an automated competency measurement support tool, QualPro-CM, focusing on the functions and modules as well as its design philosophy. This tool is developed based on the client/server architecture incorporating the use of Web-based Microsoft development tools.